A radioligand binding assay for the insulin-like growth factor 2 receptor - Potalitsyn, Pavlo; Selicharová, Irena; Sršeň, Kryštof; Radosavljević, Jelena; Marek, Aleš; Nováková, Kateřina; Jiráček, Jiří; Žáková, Lenka (PloS one, 2020)
Insulin-like growth factors 2 and 1 (IGF2 and IGF1) and insulin are closely related hormones that are responsible for the regulation of metabolic homeostasis, development and growth of the organism. Physiological functions of insulin and IGF1 are relatively well-studied, but information about the role of IGF2 in the body is still sparse. Recent discoveries called attention to emerging functions of IGF2 in the brain, where it could be involved in processes of learning and memory consolidation. It was also proposed that these functions could be mediated by the receptor for IGF2 (IGF2R). Nevertheless, little is known about the mechanism of signal transduction through this receptor. Here we produced His-tagged domain 11 (D11), an IGF2-binding element of IGF2R; we immobilized it on the solid support through a well-defined sandwich, consisting of neutravidin, biotin and synthetic anti-His-tag antibodies. Next, we prepared specifically radiolabeled [.sup.125 I]-monoiodotyrosyl-Tyr2-IGF2 and optimized a sensitive and robust competitive radioligand binding assay for determination of the nanomolar binding affinities of hormones for D11 of IGF2. The assay will be helpful for the characterization of new IGF2 mutants to study the functions of IGF2R and the development of new compounds for the treatment of neurological disorders.